Anthracycline treatment, cardiovascular risk factors and the cumulative incidence of cardiovascular disease in a cohort of newly diagnosed lymphoma patients from the modern treatment era. Issue 8 (27th May 2021) - Boddicker, Nicholas J.; Larson, Melissa C.; Castellino, Alessia; Herrmann, Joerg; Inwards, David J.; Thanarajasingam, Gita; Maurer, Matthew J.; Allmer, Cristine; Witzig, Thomas E.; Nowakowski, Grzegorz S.; Habermann, Thomas M.; Villarraga, Hector R.; et al.
Abstract: The development of cardiovascular disease (CVD) in long‐term survivors of lymphoma is of increasing importance. Here, we characterize the cumulative incidence and risk factors for CVD in lymphoma patients diagnosed in the current treatment era. From 2002–2015, newly diagnosed lymphoma patients (>18 years) were enrollment into a prospective cohort study that captured incident CVD, consisting of congestive heart failure (CHF), acute coronary syndrome (ACS), valvular heart disease (VHD), and arrhythmia. The cumulative incidence of CVD was calculated with death modeled as a competing risk. We estimated the association of treatment with anthracyclines or radiotherapy and traditional CVD risk factors with incidence of CVD using hazard ratios (HR) and 95% confidence intervals (CI) estimated from Cox regression. After excluding prevalent CVD at lymphoma diagnosis, the study consisted of 3063 patients with a median age of 59 years (range 18–95). The cumulative incidence of CVD at 10‐years was 10.7% (95% CI, 9.5%–12.1%). In multivariable analysis, increasing age (HR = 1.05 per year, p < 0.001), male sex (HR = 1.36, p = 0.02), current smoker (HR = 2.10, p < 0.001), BMI > 30 kg/m 2 (HR = 1.45, p = 0.01), and any anthracycline treatment (HR = 1.57, p < 0.001) were all significantly associated with risk of CVD. Anthracyclines were associated with increased risk of CHF (HR = 2.71, p < 0.001) and arrhythmia (HR = 1.61, p < 0.01), but not VHD (HR = 0.84, p = 0.58) or ACS (HR = 1.32, p = 0.24) after adjustment for CVD risk factors. Even in the modern treatment era, CVD remains common in lymphoma survivors and preventive efforts are required that address both treatment and CVD risk factors.